Pengaruh Kepemilikan Asing, Intangible Asset, dan Kebijakan Dividen Terhadap Transfer Pricing - Setyoningsih, Oktaviana; Pabulo, Azfa Mutiara Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research is motivated by the prevalence of transfer pricing practices in multinational companies associated with foreign ownership, intangible assets, and dividend policy. The purpose of this study is to examine the influence of these three variables on transfer pricing in multinational manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The analysis was conducted using panel data regression using EViews 12, while descriptive analysis and classical assumption tests used SPSS 25. The research sample consisted of 15 companies selected using a purposive sampling method. Transfer pricing variables were measured by Related Party Transactions (RPT), foreign ownership with a percentage of foreign shares above 20%, intangible assets with a dummy variable, and dividend policy with the Dividend Payout Ratio (DPR). The results showed that foreign ownership had no significant effect on transfer pricing (prob = 0.12; p > 0.05), while intangible assets (prob = 0.27; p > 0.05) and dividend policy (prob = 0.29; p > 0.05) did not have a significant effect.